URBAN FARMING BASED FAMILY FOOD RESILIENCE IN AN ISLAMIC PERSPECTIVE - Nur Choiro Siregar (PT Akselerasi Karya Mandiri, 2025)
Family food resilience remains a major challenge in urban areas with limited land availability, causing communities to rely heavily on imported food rather than optimizing household yards through urban farming. Limited technical knowledge further hinders the effective use of small spaces despite the economic and ecological benefits of urban farming. This study examines the role of urban farming in strengthening family food resilience by integrating Islamic values. Using a qualitative approach through a literature review of 24 scientific journals, the analysis was guided by Islamic principles and previous empirical findings. The results show that incorporating Islamic values into urban farming enhances fresh food availability, reduces household expenses, and promotes environmental awareness. These practices align with key Islamic concepts such as khalifah fil ard (stewardship), ishlah (improvement), and tawazun (balance). Overall, Islamic-based urban farming emerges as a promising strategy to promote sustainability, strengthen family food security, and support the welfare of urban communities.